National Health Observatory: A tool to strengthen the health information system for evidence-based decision making and health policy formulation in Cameroon - Viviane Fossouo Ndoungue; Christie Tiwoda; Oumarou Gnigninanjouena; Serge Bataliack; Ebongué Mbondji; Aline Labat (Elsevier, 2022)
Despite the consensus on the importance of evidence based health information for decision28 making and health policy formulation, quality information is not always available. This situation led the WHO in 2009 to recommend the establishment of an African Health Observatory and National Health Observatories. The WHO recommended 4 phases approach for the establishment of National Health Observatories was used in Cameroon: the preliminary phase, start-up, strengthening and full operation. Despite a non-optimal institutional positioning, the Cameroon's Health Observatory is in the strengthening phase and contributes to evidence-based decision making in the health system. A strong political commitment is fundamental from the beginning of the project. The establishment of National Health Observatories calls for genuine national ownership, both of the process as a whole and of the tool itself. WHO should regularly assess the progress made in the establishment of National Health Observatories in different countries and provide feedback to them. A step-by-step approach, jointly validated by national stakeholders in a roll-out plan, would be more appropriate for the sustainability of the work of National Health Observatories.